Evaluasi Pelaksanaan Pembelajaran Akidah Akhlak di Madrasah Aliyah Negeri Lhokseumawe - Dahlina, Tiha; Lemmy, Paradita Kumala (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
This study evaluates the planning, implementation, and follow-up of Akidah Akhlak learning evaluation at Madrasah Aliyah Negeri (MAN) Lhokseumawe. Employing a descriptive qualitative approach with a case study design, data were collected through observations, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman interactive model. The findings indicate that teachers plan evaluations in a structured manner, incorporating various instruments to assess cognitive, affective, and psychomotor domains. Formative evaluations are implemented continuously using a variety of methods. In contrast, summative evaluations include end-of-semester assessments (PAS), end-of-year assessments (PAT), and Madrassah exams (UM), although there is room for improvement in question validation and result analysis. Follow-up actions for evaluation results focus on providing feedback, adjusting teaching strategies, and implementing remedial and enrichment programs. Despite the comprehensive evaluation practices at MAN Lhokseumawe, areas requiring enhancement include the consistency of portfolio instruments and the depth of summative evaluation data analysis. Consequently, strengthening teachers' understanding of evaluation data analysis and instrument consistency can further optimize the Akidah Akhlak learning process.